Side effects of drugs annual - de Silva, H.J. (Elsevier, 2000)
This chapter provides an overview of gastrointestinal drugs. Some of the drug classes discussed include antacids, antiemetics, ulcer healing drugs, and cholelitholytic agents—bile acids. The chapter describes the clinical use of cisapride and its risk:benefit ratio in children. The most common adverse effects are diarrhea, abdominal cramps, borborygmi, and colic. Serious adverse events are rare and include isolated cases of extrapyramidal reactions, seizures in epileptic patients, cholestasis, and ventricular dysrhythmias, anorexia, and enuresis. Coadministration of anticholinergic drugs may compromise the beneficial effects of cisapride. Several treatments are available for promoting the healing of gastric and duodenal ulcers associated with the use of non-steroidal anti-inflammatory drugs (NSAIDs). They include histamine receptor antagonists, proton pump inhibitors, and prostaglandin analogues. Proton pump inhibitors can interact with other drugs by increasing gastric pH, inhibiting hepatic cytochrome P450, or inducing specific isoforms of this enzyme system. However, drug interactions involving these isoenzymes and omeprazole or lansoprazole are uncommon and generally appear to be clinically unimportant.
Keywords: Gastrointestinal; Drugs